(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
This study examines strategies for managing and resolving religious conflicts in Madura through the use of local wisdom of the local community. This research is a field study conducted based on the type of qualitative research. There are two data used in this research, primary data and secondary data. After using field data analysis based on sociological theory, in this case Galtung’s conflict theory, this study found that the use of local wisdom in efforts to mitigate and resolve religious conflicts in Madura is by utilizing and prioritizing local community religious leaders. In the context of Madurese society, the single most charismatic, influential and well-respected local religious figure among Madurese people is the kyai. In general, the influence and charisma of kyai in Madura is obtained because he (kyai) has sufficient and complete social capital, this social capital includes power, knowledge and ideology. Armed with these three social capitals, kyai can position themselves as intermediaries or mediators, carrying out conflict intervention functions so that the process and efforts to handle religious conflicts in Madura are optimal and good